2022
DOI: 10.3390/ijms23052855
|View full text |Cite
|
Sign up to set email alerts
|

NSAID-Based Coordination Compounds for Biomedical Applications: Recent Advances and Developments

Abstract: After the serendipitous discovery of cisplatin, a platinum-based drug with chemotherapeutic effects, an incredible amount of research in the area of coordination chemistry has been produced. Other transition metal compounds were studied, and several new relevant metallodrugs have been synthetized in the past few years. This review is focused on coordination compounds with first-row transition metals, namely, copper, cobalt, nickel or manganese, or with zinc, which have potential or effective pharmacological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 158 publications
(221 reference statements)
1
5
0
Order By: Relevance
“…Except for 1d, all ligands were more active than diclofenac. For the ligand 1d (EC50 = 109.342 ± 0.297 mg/mL) it is also important to mention that the complexation with all used metals gives complexes (2d, 3d, 4d) with an improved anti-inflammatory effect shown in this test (EC50 = 40.620 -52.276 mg/mL) which is in agreement with literature data [34].…”
Section: Erythrocyte Membrane Stabilisation Assaysupporting
confidence: 91%
See 1 more Smart Citation
“…Except for 1d, all ligands were more active than diclofenac. For the ligand 1d (EC50 = 109.342 ± 0.297 mg/mL) it is also important to mention that the complexation with all used metals gives complexes (2d, 3d, 4d) with an improved anti-inflammatory effect shown in this test (EC50 = 40.620 -52.276 mg/mL) which is in agreement with literature data [34].…”
Section: Erythrocyte Membrane Stabilisation Assaysupporting
confidence: 91%
“…A wide range of metal complexes are reported in the literature, such as Li, Mg, Al, K, Ca, Fe, Co, Ga, As, Sr, Y, Zr, Pd, Ag, Sb, Sm, Lu, Pt, Au, Hg, Bi and Ra complexes, which proved to have important biological effects [18,21]. Recent scientific data supports that NSAID-metal complexes exhibit improved anti-inflammatory properties in comparison to parent NSAIDs and, even more, induce other important biological effects [5,22,29,34,35]. For example, cobalt (II), manganese (II), or zinc (II) complexes of some diclofenac derivatives exhibited very promising anti-inflammatory effects and, in addition, proved to have important antioxidant effects not present in diclofenac [32,33,46].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed the potential of the Ni(II) complexes as a prototype of new antitumor drugs. Despite anti-cancer activity already having been demonstrated for Ni(II) complexes which targeted DNA ( Zhang et al, 2018 ) and kinase proteins ( Santos et al, 2022 ), this is not a frequent metal in pharmacological studies (Cu and Zn are much more usual to be found in the specialized literature, for example), making Ni(II) complexes an open field of opportunities to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these complexes were NSAID–platinum­(IV) complexes. ,, Also, there were reports of NSAID-based coordination with other metals including copper, cobalt, nickel, etc. Accordingly, the synthesis of metal–NSAID complexes is an attractive chemotherapeutic strategy to overcome multidrug resistance (MDR), improve the immune response, and inhibit inflammation-induced metastatic cancers. , As mentioned above, TrxR inhibitors (e.g., the gold complexes) may be potential ICD inducers, which elicit the DAMP approach for tumor cells, modify the state of tumor cells, and stimulate the immune response. Meanwhile, it has been proved that NSAIDs could improve the immunosurveillance, suppress the proliferation, and induce the ICD effects of colorectal tumor cells .…”
Section: Introductionmentioning
confidence: 99%